An Evaluation of the Fasciola hepatica miRnome Predicts a Targeted Regulation of Mammalian Innate Immune Responses - Ricafrente, Alison; Nguyen, Hieu; Tran, Nham; Donnelly, Sheila (Frontiers in Immunology, 2021)
Understanding mechanisms by which parasitic worms (helminths) control their hosts’ immune responses is critical to the development of effective new disease interventions. Fasciola hepatica, a global scourge of humans and their livestock, suppresses host innate immune responses within hours of infection, ensuring that host protective responses are quickly incapacitated. This allows the parasite to freely migrate from the intestine, through the liver to ultimately reside in the bile duct, where the parasite establishes a chronic infection that is largely tolerated by the host. The recent identification of micro(mi)RNA, small RNAs that regulate gene expression, within the extracellular vesicles secreted by helminths suggest that these non-coding RNAs may have a role in the parasite-host interplay. To date, 77 miRNAs have been identified in F. hepatica comprising primarily of ancient conserved species of miRNAs. We hypothesized that many of these miRNAs are utilized by the parasite to regulate host immune signaling pathways. To test this theory, we first compiled all of the known published F. hepatica miRNAs and critically curated their sequences and annotations. Then with a focus on the miRNAs expressed by the juvenile worms, we predicted gene targets within human innate immune cells. This approach revealed the existence of targets within every immune cell, providing evidence for the universal management of host immunology by this parasite. Notably, there was a high degree of redundancy in the potential for the parasite to regulate the activation of dendritic cells, eosinophils and neutrophils, with multiple miRNAs predicted to act on singular gene targets within these cells. This original exploration of the Fasciola miRnome offers the first molecular insight into mechanisms by which F. hepatica can regulate the host protective immune response.